PUBLIC RECOGNITION OF THE SOCIAL ENTREPRENEURSHIP SECTOR IN LATVIA AND THE WAY FORWARD - Casno, Kristīne; Sloka, Biruta (University of Latvia, 2022)
In Latvia social entrepreneurship is relatively new, but highly potential. Especially over the last 5 years many incremental positive developments have resulted in 193 social enterprises with the official status as of September 30, 2021, the overall competitiveness of the sector remains relatively low as social enterprises struggle with digital skills, sales and marketing. Many are fighting to make ends meet with limited budgets and high degree of uncertainty, especially under the circumstances of the Covid-19 pandemic. Research findings from 2019 reveal average or below average information levels within Latvian society and confirm the significant positive role awareness and information about the social entrepreneurship sector within society plays in generating sales in the social economy sector. The purpose of the research is to provide the newest and in-depth data on the degree of public recognition and awareness of the social entrepreneurship sector in order to determine potential directions for improvement with practical implications for social enterprises as well as public authorities. Research methods are analysis of previously conducted research and survey of 1026 respondents. Research results indicate a need to delineate the concept of a social enterprise by clearly distinguishing it from such organization types as a non-governmental organization or charity. Significant number of respondents possess a general idea of what social entrepreneurship is about and express willingness to support social economy by purchasing social enterprise products and services. Challenges remain in the need to increase awareness and reduce the presence of various misconceptions about social enterprises and social entrepreneurship.
The research was supported by the NATIONAL RESEARCH PROGRAMME “LATVIAN HERITAGE AND FUTURE CHALLENGES FOR THE SUSTAINABILITY OF THE STATE” project “CHALLENGES FOR THE LATVIAN STATE AND SOCIETY AND THE SOLUTIONS IN INTERNATIONAL CONTEXT" (INTERFRAME-LV, Project No.VPP-IZM-2018/1-0005).
Keywords: public recognition; social entrepreneurship; social enterprise; Latvia; Research Subject Categories::SOCIAL SCIENCES::Business and economics